Portraying Young Learners' Language Learning Strategies: A Case Study from EFL Teachers' Voices - Marsevani, Maya; Micheline Slikker, Gabriela; Lady Pratiwi, Theodesia; Nugraha, Hendra (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
This study aims to investigate how EFL teachers decide on and adapt teaching strategies for young learners in ELT classrooms and explore strategies teachers use to encourage independent language learning. The research was conducted as a case study in an academic English course in Batam and involved three experienced EFL teachers. Data collection methods included observation checklists, semi-structured interviews, and analysis of lesson plans. Descriptive analysis was applied to observation checklists and document reviews, while thematic analysis was used for interview data. The findings underscore the importance of flexible teaching methods that emphasize student engagement and align instructional activities with learning goals. They highlight the necessity of customizing teaching strategies to students' backgrounds and interests and efficiently utilizing classroom resources to promote active learning and enhance educational outcomes in EFL contexts, thereby fostering autonomous learning among students. In conclusion, effective EFL teaching involves integrating student engagement, active learning strategies, customized teaching approaches, and adequate classroom resources. The implications stress the importance of a holistic approach to EFL learning that prioritizes student engagement, active and independent learning, effective technology use, and continuous professional development for EFL teachers